Chirality-driven molecular packing structure difference and potential application for 3D printing of a series of bola-type Ala–Phe dipeptides. (23rd November 2020) - Zheng, Cheng; Lin, Shuwei; Hu, Chuanjiang; Li, Yi; Li, Baozong; Yang, Yonggang
Abstract : For bola-type dipeptides based on Ala–Phe building block, the chirality of Phe residue at C-terminal determined the handedness of self-assemblies and stacking chirality of carbonyl groups. Abstract : A series of bola-type dipeptides based on an Ala–Phe building block was synthesized by altering the chirality of Ala and Phe. They were able to self-assemble into right- or left-handed helical nanofibers in a mixture of methanol and water. Both the handedness of the nanofibers and that of the molecular stacking were controlled by the chirality of the phenylalanine residue. 1 H NMR, circular dichroism and FT-IR characterizations indicated that the formation of the nanofibers was driven by the hydrophobic association of the hydrocarbon chains, π–π stackings of the phenyl rings and hydrogen bonds. X-ray diffraction patterns showed that the diastereoisomers packed into different structures. These bola-type Ala–Phe dipeptides can be potentially used for 3D printing.